PENERAPAN METODE EJA DENGAN MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS I MI MIFTAHUL ULUM BANJARSARI - Rizqi Farida; Melani Albar (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
This study aims to describe the application of the spelling method with flash card in improving the reading ability of Class I students at MI Miftahul Ulum, Banjarsari Hamlet, Bululawang District. The results showed that the reading ability of Class I students of MI Miftahul Ulum Dusun Banjarsari Bululawang District was proven to have increased through the application of the spelling method with flash card, this was marked by an increase in the average value of the psychomotor test, from 59.26 in the Pre-Cycle implementation, to 68.52 in the implementation of Cycle I, and increased again to 81.11 in the implementation of Cycle II. Likewise, the percentage of mastery learning also increased from 29.63% in the Pre-Cycle implementation, to 59.26% in the Cycle I implementation, even in the Cycle II implementation it increased to 92.59%.